Effect of Mg on Al-Mg Alloy and Electroless Ni-P Codeposition of nano-Al2O3: Mechanical, Wear, and Corrosion Resistance Properties - Daniel, Shetha; Banerjee, Nilotpal; Majumder, Manik; Chitrapady Vishweshwara, Sudhir (Trends in Sciences, 2023)
The addition of magnesium to Aluminum alloys has become increasingly popular due to their lightweight, high strength, and corrosion resistance properties. Our research on high-content Mg doped 90, Al-10 wt% Mg alloy has shown that coating it with electroless Ni-P and codepositing nano-Al2O3 (0, 2.5, 5 and 7.5 wt%) can significantly improve its mechanical properties, resistance to wear & tear, and even corrosion resistance. The electroless Ni-P-5 wt% Al2O3 composite displayed a wear rate of 0.65×10−3 g/m at 12 N, a microhardness value of 598 HV, and remarkable thermal shock resistance. A strong and uniform bond was formed between the coating and substrate, and no delamination or cracking was observed. Polarisation curves in 3.5 wt% NaCl solution showed that the corrosion potential of the 90, Al-10 wt% Mg alloy was higher than that of Ni-P and Ni-P-nano Al2O3 composites, indicating that the incorporation of nano-Al2O3 into the Ni-P electroless bath provides superior corrosion protection. This cost-effective and simple approach makes the Ni-P-5 wt% Al2O3 nanocomposite coating an ideal choice for shielding Al-Mg alloys from corrosion. HIGHLIGHTS We examine the magnesium content in Al-Mg alloy Electroless Ni-P-5 wt% Al2O3 coating could improve the anti-corrosion properties of Al-Mg alloy The thermal shock test showed that the alloy had good thermal stability Microhardness and wear resistance increase with the addition of nano Al2O3 particles The electroless Ni-P-5 wt% Al2O3 composite shows a wear rate of 0.65×10−3 g/m at 12 N GRAPHICAL ABSTRACT